AN ANALYSIS OF READING MATERIALS IN “BRIGHT AN ENGLISH COURSE FOR JUNIOR HIGH SCHOOL STUDENT” YEAR VIII PUBLISHED BY ERLANGGA BASED ON THE 2013 ENGLISH STANDARD CURRICULUM (RETAIN, 2015)
ABSTRACT Recently, the 2013 curriculum has been launched by PeraturanPemerintah No.32 Th. 2013 the educational system of Indonesia has launched the 2013 curriculum which the aim to prepare Indonesian people to be religious, productive, creative and innovative.From the new launched curriculum also make the change in learning sources. One of them is textbook that is conducting in 2013 curriculum. Because it is an important component that should be considered by the teacher in order to teach well. Textbook consist of several material that assist teaching and learning process. Brown (2001:136) says that the textbook is the most common material or teaching and learning. Richard (2001: 251) also says that the key component of language teaching is teaching material. Selecting the best textbook is considering difficult for some teachers. Although there are many textbooks which are claimed suitable with the 2013 curriculum, there is no guarantee whether the textbook is relevant to the standard competences of the 2013 English curriculum. To solve this problem, the researcher focused this study: 1) to describe the relevance of the reading materials in textbook entitled “BRIGHT” to the 2013 English Standard Competence in term of cognitive aspects, 2) to describe the relevance of the reading materials in textbook entitled “BRIGHT” to the 2013 English Standard Competence in term of psychomotor aspects. This study was designed in descriptive qualitative research. The instrument used to collect the data is observation in the form of checklists. After being analyzed, it is found that all chapters in the first semester are not fully covering the indicators of cognitive aspects in the basic competences three. Meanwhile, some of the reading materials are irrelevant in terms of psychomotor aspects. After all, the researcher argues that this textbook is still appropriate to be used, since the materials are mostly relevant with the 2013 curriculum. This textbook is still suitable to be used in order to help teacher and students in the process of teaching and learning, but is not fully for reading. Key words: analysis, relevance, reading materials, textbook, the 2013 Curriculum ABSTRAK Baru-baru ini, 2013 kurikulum telah diluncurkan oleh PeraturanPemerintah No.32 Th. 2013 sistem pendidikan Indonesia telah meluncurkan 2013 kurikulum yang bertujuan untuk mempersiapkan masyarakat Indonesia untuk menjadi religius, produktif, kreatif dan innovative. Dari kurikulum diluncurkan baru juga membuat perubahan dalam sumber-sumber belajar. Salah satunya adalah buku yang sedang melakukan pada tahun 2013 kurikulum. Karena merupakan komponen penting yang harus dipertimbangkan oleh guru untuk mengajar dengan baik. Buku terdiri dari beberapa bahan yang membantu proses belajar mengajar. Brown (2001: 136) mengatakan bahwa buku teks adalah bahan yang paling umum atau pengajaran dan pembelajaran. Richard (2001: 251) juga mengatakan bahwa komponen kunci dari pengajaran bahasa adalah mengajar materi. Memilih buku yag terbaik sulit bagi beberapa guru. Meskipun ada banyak buku yang diklaim sesuai dengan kurikulum 2013, tidak ada jaminan apakah buku tersebut relevan dengan kompetensi standar dari 2013 kurikulum bahasa Inggris. Untuk mengatasi masalah ini, peneliti memfokuskan penelitian ini: 1) untuk menggambarkan relevansi bahan bacaan dalam buku berjudul